PEMBELAJARAN MENULIS TEKS CERPEN DENGAN MENGGUNAKAN METODE PEMBELAJARAN BERBASIS MASALAH PADA SISWA KELAS XI SMK CITRA PEMBAHARUAN - Silvya Mega Dewi; Teti Sobari (IKIP Siliwangi, 2018)
This research background because there are still many students who are not interested in writing short stories and the author has an idea to create the ability and willingness so that students interested in writing short stories text. The purpose of this research is to know the effectiveness of problem-based learning method. The method used in this study is a quasi-experimental method with the type of non-equivalent control group design, Based on the observer's observation that 100% of teachers are able to implement the process of writing short story text using problem-based learning method well. Based on the assessment by observer that 93.3% of students are able to follow the learning process of reading exposition text using problem-based learning method well. the results of the initial test and final tests in both classes obtained the average value of the final test of the experimental class of 77, the control class to obtain the average final test score of 68. Manwhitney test hypothesis test obtained 0.000 this means Ho is rejected and Ha accepted meaning there is a significant difference in the ability to write short story text using problem-based learning method. Student response showed positive response, evidenced by the number of positive statements of students 62% and 38% negative statements.) Population in this study is all students of class XI SMK Citra Pembaharuan with two class samples of 60 students.